2022
DOI: 10.1097/iae.0000000000003588
|View full text |Cite
|
Sign up to set email alerts
|

Topical Carbonic Anhydrase Inhibitors in the Long-Term Treatment of Juvenile X-Linked Retinoschisis

Abstract: Purpose: To describe the response to long-term topical dorzolamide treatment in patients with juvenile X-linked retinoschisis and cystic-like foveal lesions.Methods: This was a retrospective interventional case series that included 18 eyes of 10 patients with genetically confirmed juvenile X-linked retinoschisis examined at the Cleveland Clinic Cole Eye Institute, a tertiary referral center, between 2005 and 2021. Patients were treated with topical 2% dorzolamide two to three times daily in both eyes. Two eyes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…The only prospective study by Pennesi et al exhibited no morphological or functional improvement over an 18-month follow-up in XLRS patients undergoing CAI therapy ( 33 ). On the other hand, several retrospective studies have reported a reduction in ICC volume along with improvement in BCVA in a few ( 22 , 32 , 34 37 ). However, these studies employed varied treatment protocols and follow-up durations with no control group.…”
Section: Discussionmentioning
confidence: 98%
“…The only prospective study by Pennesi et al exhibited no morphological or functional improvement over an 18-month follow-up in XLRS patients undergoing CAI therapy ( 33 ). On the other hand, several retrospective studies have reported a reduction in ICC volume along with improvement in BCVA in a few ( 22 , 32 , 34 37 ). However, these studies employed varied treatment protocols and follow-up durations with no control group.…”
Section: Discussionmentioning
confidence: 98%
“…CAIs have been used to treat schisis or CME, which is achieved by modulating carbonic anhydrase IV receptors on the RPE membrane or by enhancing fluid transport [44,45]. However, the effectiveness of CAIs varies, and reports suggest that their impact is more visible in improving central foveal thickness and less so in improving visual acuity [40,46,47].…”
Section: Management and Prognosismentioning
confidence: 99%
“…Several other gene-based trials for XLRS are ongoing (NCT05878860, NCT02317887, NCT05814952). In several small case series, both oral acetazolamide and topical dorzolamide have been found to reduce foveal schisis and improve vision (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). The purpose of this study is to investigate whether carbonic anhydrase inhibitors (CAIs) reduce the incidence of complications from XLRS, including macular atrophy, retinal tears, and retinal detachment (RD).…”
Section: Introductionmentioning
confidence: 99%